Modelos numéricos a usar na modelação da alvenaria de pedra - Alexandre Costa (2008)
Different numerical models used to reproduce stone masonry are succinctly presented on this work, starting from micro-modelling up to macro-models description. Besides an overview of available models, particular relevance is given to micro-modelling for which a specific model is described with more detail in order to support a case study referring to a stone masonry wall panel extracted from an existing Azorian construction. The panel was experimentally tested in laboratory under cyclic in-plane loading and results are herein presented, as well as a comparison with numerical results obtained from a micro-modelling simulation.